Corporate Social Responsibility and Financial Performance : Moderating Impact of Product Market Competition - Sharma, Deepa; Chakraborty, Suman (Indian Journal of Finance, 2024)
Purpose : This paper, which is based on the idea of â€œstrategic CSR,â€ examined how product market competition (PMC) affected the relationship between Indian companiesâ€™ financial performance (FP) and corporate social responsibility (CSR). Methodology : The study was conducted on 534 manufacturing firms listed on Indiaâ€™s National Stock Exchange from 2016 to 2021. Based on the Hausman Specification test, this study used a fixed effects panel regression model to test the stated relationships. Findings : A review of 3,204 firm-year observations revealed that CSR had a detrimental effect on firmsâ€™ FP. The relationship between CSR and FP showed a positive moderating influence of PMC, supporting the â€œstrategic CSRâ€ approach, which contends that CSR enhanced FP for businesses operating in a competitive market. Practical Implications : This analysis validated empirical precedents that showed a favorable association between competition and company FP and a negative influence of CSR. The target audience for this study included academics, managers, stakeholders, and users of CSR data due to the importance of corporate responsibility in today’s world. Originality : In the Indian context, this study is the first attempt, as far as we are aware, to examine the moderating effect of PMC on the link between CSR and FP.